0370 Telehealth Delivery Of Group Cbt-i Is Non-inferior To In-person Treatment In Veterans With Ptsd. (27th April 2018) - Gehrman, P; Bellamy, S; Medvedeva, E; Barilla, H; Brownlow, J; Prigge, J; Rehman, W; Kuna, S T
Abstract: Introduction: Insomnia is highly prevalent in veterans with Posttraumatic Stress Disorder (PTSD). Cognitive behavioral therapy for insomnia (CBT-I) has been shown to be efficacious in this population, but access to treatment is often limited. Delivery of CBT-I in a group format can increase the reach of providers. Video telehealth technology can further increase this reach by connecting the provider to patients at a distant location. The primary hypothesis of this cluster-randomized trial was that telehealth delivery of CBT-I is non-inferior to in-person treatment. Methods: Veterans with current PTSD on the Clinician Administered PTSD Scale and Insomnia Severity Index (ISI) score ≥ 15 were enrolled. Participants with sleep apnea on home testing had to be on PAP treatment for at least 3 months. Participants were randomized to receive group CBT-I in-person or by video telehealth. The primary endpoint was change in ISI score from baseline to the 3-month follow up assessment. Non-inferiority was defined as a difference in change scores between groups <2.0 points. We report here the results of intent-to-treat analyses. Results: 95 participants were enrolled and randomized to in-person (n=46) or telehealth (n=49) treatment (mean age 55.6 ± 12.1 yr; 91.4% males; 42.2% African American). In Intent-to-Treat analyses, the mean change in total ISI score was 6.48 for in person CBT-I and 4.45 for telehealth CBT-I. This difference in efficacy between groups was less than the pre-specified margin for non-inferiority, indicating that CBT-I delivered by telehealth was not clinically inferior to in-person treatment. Conclusion: These results indicate that telehealth delivery of group CBT-I is not clinically inferior to in-person care. Given the importance of treating insomnia in the PTSD population, improving access to care is essential. Since widespread implementation of CBT-I is limited by the lack of trained clinicians, telehealth can greatly improve access to care, particularly for those in rural locations. Support (If Any): VHA HSR&D HX000833.